Dissociative electron attachment to gold(I)-based compounds: 4,5-dichloro-1,3-diethyl-imidazolylidene trifluoromethyl gold(I) - Pintea, Maria; Mason, Nigel; Peiró-Franch, Anna; Clark, Ewan; Samanta, Kushal; Glessi, Cristiano; Schmidtke, Inga Lena; Luxford, Thomas (Frontiers in Chemistry, 2023)
With the use of proton-NMR and powder XRD (XRPD) studies, the suitability of specific Au-focused electron beam induced deposition (FEBID) precursors has been investigated with low electron energy, structure, excited states and resonances, structural crystal modifications, flexibility, and vaporization level. 4,5-Dichloro-1,3-diethyl-imidazolylidene trifluoromethyl gold(I) is a compound that is a uniquely designed precursor to meet the needs of focused electron beam-induced deposition at the nanostructure level, which proves its capability in creating high purity structures, and its growing importance in other AuImx and AuClnB (where x and n are the number of radicals, B = CH, CH3, or Br) compounds in the radiation cancer therapy increases the efforts to design more suitable bonds in processes of SEM (scanning electron microscopy) deposition and in gas-phase studies. The investigation performed of its powder shape using the XRPD XPERT3 panalytical diffractometer based on CoKα lines shows changes to its structure with change in temperature, level of vacuum, and light; the sensitivity of this compound makes it highly interesting in particular to the radiation research. Used in FEBID, though its smaller number of C, H, and O atoms has lower levels of C contamination in the structures and on the surface, it replaces these bonds with C–Cl and C–N bonds that have lower bond-breaking energy. However, it still needs an extra purification step in the deposition process, either H2O, O2, or H jets.